UJI EFEKTIVITAS EKSTRAK DAUN SIRIH (PIPER BETLE L.) TERHADAP MORTALITAS LARVA ANOPHELES ACONITUS - Rochmadina Suci Bestari (Universitas Respati Yogyakarta, 2020)
Background: Diseases transmitted by mosquitoes are still a public health problem in Indonesia, one of them is malaria. Malaria is caused by plasmodium parasite spread by anopheles mosquitoes as vectors. Objective: This research aimed to find out the effectiveness of betel leaf extract (Piper betle L.) in ethanol 96% against larvae mortality of Anopheles aconitus. Method: designed as experimental laboratory with post test control group design by giving treatment Anopheles aconitus larvae with of betel leaf extract (Piper betle L.). There were 600 instar III Anopheles aconitus larvae randomly divided into 6 groups (concentrations of 0%, 0.01%, 0.03%, 0.05%, 0.07% and abate as a positive control). Each group was observed every 6 hours for 24 hours and repeated 4 times. Result: The Kruskal-Wallis test results obtained a value of p = 0,000 which means that there is a significant difference in the effects of larvacides between groups. Post-Hoc Mann-Whitney test showed that all concentrations had significant differences compared to negative controls, while positive controls with a concentration of 0.07% did not differ significantly. Conclusion: From this study it can be concluded that 0.07% has the most effective concentration of killing larvae. Betel leaf extract (Piper betle L.) is effective in killing Anopheles aconitus larvae.